High intensity running among men’s elite field hockey based on playing position / Mohd Ezwan Jamil - Jamil, Mohd Ezwan (2013)
The purpose of this study was to investigate the high intensity running demands of elite men’s field hockey using modern tracking devices which is GPS. Eighteen (N=18) elite male players (age: 27.88±1.99 years) participated in 6 matches, during which physical output of playing were quantified using GPS units and heart rate monitors. The mean of HIR frequency for (defender: 92.11±17.36, midfielder 82.66±21.15, striker: 96.94±12.66), HIR distance covered was (defender: 2116.49±351.10, midfielder: 2113.13±614.78, striker: 2351.56±297.29), HIR below 10m was (defender: 25.52±5.64, midfielder: 21.88±8.41, striker: 26.11 ±5.01) and top speed was (defender: 27.75±2.52, midfielder: 29.36±2.12, striker: 29.38±2.71). All measured variable not show significance to HIR distance covered (0.703, p < 0.05), HIR below 10m frequency (0.505, p < 0.05), HIR frequency (0.647, p < 0.05) and top speed achieved (0.468, p < 0.05). These results suggest that modern day elite field hockey is physically demanding team sport especially in high intensity running to all players of all playing positions with the exception of the goalkeeper. Quantification of the demands and outputs of the players at competitive level provides useful framework on which to develop conditioning practices. The differences in high intensity running observed for some position suggests position-specific conditioning is required at the elite level.